PENGARUH KOLEKSI PUSTAKA PRIBADI TERHADAP PERILAKU BELAJAR MAHASISWA IPII DI UIN BANDUNG - Hasna Nada Nadyrra; Lutfia Rahma; Dary Hanum Salsabila Luluah; Alyaa Nuur'Aisy; Wisnu Uriawan; Falih Ijlal Septian (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This study aims to examine the relationship between personal library ownership and learning behavior among students of the Islamic Library and Information Science Program (IPII) amid limited institutional library collections. A quantitative method with an explanatory research approach was employed to measure the level of utilization of personal collections and their influence on students’ learning behavior. Data were collected through an online Likert-scale questionnaire distributed to IPII students using random sampling techniques. Data analysis was conducted using validity and reliability tests, descriptive analysis, Pearson correlation, and simple linear regression with SPSS software. The findings indicate that although most students own a relatively small number of personal books, these collections are actively used to support understanding of course materials, completion of academic assignments, and exam preparation. Furthermore, personal library ownership has a positive effect on learning behavior, particularly in terms of learning independence, motivation, time management, material repetition, and academic confidence. The study concludes that personal libraries function as an effective alternative learning resource and play a significant role in fostering more independent, disciplined, and systematic learning behaviors among students, especially in academic environments where institutional library collections are still limited. Keywords: personal library collection; collection utilization; learning behavior; library science students; limited library resources.